Multifunctional nanoparticles for MR and fluorescence imaging - Pinho, Sonia Luzia Claro de (2012)
In the past few years a new generation of multifunctional nanoparticles (NPs) has been proposed for biomedical applications, whose structure is more complex than the structure of their predecessor monofunctional counterparts. The development of these novel NPs aims at enabling or improving the performance in imaging, diagnosis and therapeutic applications. The structure of such NPs comprises several components exhibiting various functionalities that enable the nanoparticles to perform multiple tasks simultaneously, such as active targeting of certain cells or compartmentalization, imaging and delivery of active drugs. This thesis presents two types of bimodal bio-imaging probes and describes their physical and chemical properties, namely their texture, structure, and 1H dynamics and relaxometry, in order to evaluate their potential as MRI contrast agents. The photoluminescence properties of these probes are studied, aiming at assessing their interest as optical contrast agents. These materials combine the properties of the trivalent lanthanide (Ln3+) complexes and nanoparticles, offering an excellent solution for bimodal imaging. The designed T1- type contrast agent are SiO2@APS/DTPA:Gd:Ln or SiO2@APS/PMN:Gd:Ln (Ln= Eu or Tb) systems, bearing the active magnetic center (Gd3+) and the optically-active ions (Eu3+ and Tb3+) on the surface of silica NPs. Concerning the relaxometry properties, moderate r1 increases and significant r2 increases are observed in the NPs presence, especially at high magnetic fields, due to susceptibility effects on r2. The Eu3+ ions reside in a single low-symmetry site, and the photoluminescence emission is not influenced by the simultaneous presence of Gd3+ and Eu3+. The presence of Tb3+, rather than Eu3+ ion, further increases r1 but decreases r2. The uptake of these NPs by living cells is fast and results in an intensity increase in the T1-weighted MRI images. The optical features of the NPs in cellular pellets are also studied and confirm the potential of these new nanoprobes as bimodal imaging agents. This thesis further reports on a T2 contrast agent consisting of core-shell NPs with a silica shell surrounding an iron oxide core. The thickness of this silica shell has a significant impact on the r2 and r2* relaxivities, and a tentative model is proposed to explain this finding. The cell viability and the mitochondrial dehydrogenase expression given by the microglial cells are also evaluated.